A novel adaptive non-backstepping VUFC algorithm for a class of MIMO nonlinear systems with unknown dead-zones in pure-feedback form. (February 2019) - Wang, Rui; Yu, Fu-Sheng; Liu, Yan-Jun; Wang, Jia-Yin; Yu, Lian; Zhao, Li-yun
Abstract: In this paper, based on adaptive non-backstepping design algorithm, we proposed a novel variable universe fuzzy control (VUFC) algorithm for a class of MIMO nonlinear systems with unknown dead-zone inputs in pure-feedback form. First, by introducing some new states variables and coordinate transforms, the system is converted form the state-feedback control of pure-feedback form into the output-feedback control of normal form. Secondly, different from traditional backstepping scheme, we introduce contraction–expansion factors, combine non-backstepping control technique and VUFC scheme together to construct the controllers and observers. VUFC approach is mainly based on changing the contraction–expansion factor to change the universe of the variables (which can change the interpolation node encryption). It is shown that the proposed control approach is considerably simpler and better than the backstepping-based ones and it can improve the accuracy of the system, alleviate tracking error, strong robustness. At last, according to stable positive real (SPR)-Lyapunov stability analysis, it can guarantee that all the signals in the closed-loop system are bounded and the output can tack the reference signal to a small neighborhood of the origin. Simulations results are illustrated that the effectiveness of the proposed VUFC approach.